Preparation of (177Lu-DOTA)n-PAMAM-[Nimotuzumab-F(abâ)2] as a Therapeutic Radioimmunoconjugate for EGFR Overexpressed Cancers Treatment - Titis Sekar Humani; Sutari Sutari; Triningsih Triningsih; Martalena Ramli; Rien Ritawidya; Ratna Dini Haryuni (Institute for Research and Community Services (LPPM) ITB, 2017)
Intact monoclonal antibodies with a high molecular weight tend to have a poor pharmacokinetic profile and tumor penetration, and potential for eliciting host antibody responses. F(abâ)2 fragments smaller than intact monoclonal antibodies that still maintain antigen binding could solve this problem. The objective of this study was to optimize the digestion process of nimotuzumab, an anti-EGFR monoclonal antibody, into its F(abâ)2 fragment and investigate its potential as a therapeutic radioimmunoconjugate. Optimal conditions for digestion of nimotuzumab to its F(abâ)2 fragment were found to be 6 hours of digestion time with a pH of 3.5 and 1:100 mol ratio of pepsin to nimotuzumab. The purity of the F(abâ)2-nimotuzumab was confirmed by SDS-PAGE and HPLC analysis. Prior to its labeling with lutetium-177 radionuclide, the nimotuzumab-F(abâ)2 was conjugated to DOTA-PAMAM dendrimer [DOTA denotes 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid, PAMAM denotes poly(amidoamine)] to form conjugate of (DOTA)n-PAMAM-[nimotuzumab-F(abâ)2]. Radiolabeling of DOTA-PAMAM-[nimotuzumab-F(abâ)2] conjugate with 177Lu resulted in (177Lu-DOTA)n-PAMAM-[nimotuzumab-F(abâ)2] with radiochemical purity > 99% after purification with a PD-10 column. Further studies still need to be performed in order to confirm the potential of this radioimmunoconjugate as a radioimmunotherapeutic agent for EGFR overexpressed cancers.